The Effect of Business Scale in Moderating the Intention to Adopt QRIS: an Approach from The Theory of Acceptance and Use of Technology (UTAUT) - Wati, Liana Cipto (University of Merdeka Malang, 2024)
This study aims to identify factors that influence the intention of Micro, Small and Medium Enterprises (MSMEs) in adopting QRIS (Quick Response Code Indonesian Standard) as a digital payment tool. Using the Unified Theory of Acceptance and Use of Technology (UTAUT) theoretical framework, this study examines the effect of Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), and Facilitating Conditions (FC) variables on the intention to adopt QRIS. In addition, this study also introduces business scale as a moderating variable to explore how differences in business size can affect the relationship between these factors and adoption intention.This study uses a survey method by collecting data from 206 respondents who are MSME actors in Indonesia. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that EE, SI, and FC have a positive and significant influence on QRIS adoption intention, while PE has no significant influence. The findings also reveal that business scale has a moderating role in the effect of FC on QRIS adoption intention, suggesting that small businesses need more adequate support to adopt new technologies.This study makes a theoretical contribution by extending the UTAUT model through the addition of moderating variables of business scale, as well as providing practical implications for technology developers and policy makers to optimize technology adoption strategies in the MSME sector. The findings highlight the importance of paying attention to the specific needs and capacities of MSMEs in supporting digital transformation, as well as ensuring adequate facilities and technical support are available to encourage wider technology adoption.